Identifying wine grape aromatic maturity using e-nose and GC-MS: the case of Nerello Mascalese grapes from two contrade of the Etna area - Umberto Tarì; Stefano Pettinelli; Alessandro Bianchi; Matteo Pollon; Gianmarco Alfieri; Clara Vitaggio; Onofrio Corona; Margherita Modesti; Fabrizio Onofrio Fiorino; Andrea Bellincontro; Fabio Mencarelli (OENO One, 2024)
A study of aromatic maturity of Nerello Mascalese grapes from two districts (“Contrade”) of the Etna area was carried out using gas chromatography-mass spectrometry (GC-MS) and electronic nose (E-nose). To validate our hypothesis regarding the potential use of E-nose for aromatic maturity, two vineyards with different characteristics (08 Alto and Solicchiata) were used. Grapes were sampled at 18°, 21° and 23°Brix. Regarding the phenol maturity index, total anthocyanins reached a peak at the second sampling in 08 Alto grapes, while in Solicchiata they constantly increased. The ratio total anthocyanins: total polyphenols in 08 Alto grapes increased from 0.14 to 0.33, and in Solicchiata from 0.17 to 0.23. As regards grape volatile organic compounds (GVOCs) for the aromatic maturity index, in Solicchiata the concentrations of glycosylated benzenoids and C13-norisoprenoids were much higher than in 08 Alto, and the concentration decreased during maturity (opposite trend to the anthocyanins); by contrast, in 08 Alto, concentrations peaked at the second sampling time (as with the anthocyanins). The E-nose results did not completely coincide with the GVOCs pattern, but they discriminated the maturity stages very well. However, the different metallo-porphyrins responded differently depending on the class of GVOCs, highlighting very promising results in terms of GVOCs non-destructive prediction by means of principal component regression (PCR) application. E-nose shows potential for easy use with rapid PCR for the monitoring of the aromatic maturity of Nerello Mascalese grapes.